The Influence of Organizational Culture and Workload on Employee Work Performance at PT Angkasa Pura I (Persero) Ahmad Yani International Airport Semarang - M Hafiidh Lutvi; Rara Ririn Budi Utaminingtyas; Umar - Farouk (JOBS (Jurnal Of Business Studies), 2021)
This study aims to determine the influence of the organizational culture and workload on employee work achievement at PT Angkasa Pura I (Persero) Jenderal Ahmad Yani International Airport Semarang both simultaneously and partially. Data collection methods used in this study were observation, interviews and questionnaires. The population used in this study was 115 employees of PT Angkasa Pura I (Persero) Jenderal Ahmad Yani International Airport Semarang. The sample in this study was 60 employees of PT Angkasa Pura I (Persero) Jenderal Ahmad Yani International Airport Semarang. The sampling technique used is purposive sampling. The types ofdata used in this study are primary data and secondary data. The data analysis model used is multiple linear regression. Data analysis techniques for hypothesis testing used the F test, t test and R2 test. This study indicates that (1) organizational culture has a positive and significant effect on employee work achievement. (2) workload has a significant positive effect on employee work achievement. (3) organizational culture and workload have a significant effect on employee work achiement, and (4) partially the dominant influence is workload. Organizational culture and workload contributed 37,3% to employee work achievement. This means that 62,7% is explained by other factors not examined in this study. The next researcher should be able to use variables that are not used in this study. namelywork discipline, work environment, loyalty, work motivation and job satisfaction.